After 40 Years, Nostra Aetate's Christological Implications - Henrix, Hans Hermann (Studies in Christian-Jewish Relations, 2011)
In reflecting on the Christological statements in Nostra Aetate, Â§4 and on their implications, both the strongest link between Christians and Jews and their deepest difference have become apparent to Christian theology. The essential Christian conviction that the crucified and risen Jesus Christ is the Messiah and beyond that the Incarnate Son of God is not only denied by Jews, but is incomprehensible for them. Jewish objections have caused Christian theology to ask whether it is possible for it to say something positive as regards Jewish hope in the Messiah, a hope which also says “no” to Christians’ faith in Christ. The Pontifical Biblical Commission picked up on this question in a positive way in its text of the year 2001, The Jewish People and Their Sacred Scriptures in the Christian Bible. In addition, Jewish criticism of the Christian idea of the Incarnation, not least in discussions of shituf ("association"), has brought a new awareness of the importance for Christian-Jewish dialogue of the teaching of the Council of Chalcedon on the preservation of the character of each nature unified in Christ.